(untitled) (Eureka Journal of Civil, Architecture and Urban Studies, 2026)
This scientific article examines the conservation methods applied to wooden historical architectural monuments, using Japanese historical buildings as a representative case study. The research focuses on traditional and modern conservation approaches, structural and material preservation techniques, and philosophical principles underlying Japanese heritage conservation practices. The study analyzes internationally recognized conservation doctrines alongside Japan’s indigenous restoration traditions, emphasizing minimal intervention, material authenticity, and cyclical reconstruction practices. The findings highlight the effectiveness of Japan’s integrated conservation model and its relevance for global heritage preservation strategies.